Stochastic density effects on adult fish survival and implications for population fluctuations. (26th November 2015) - Okamoto, Daniel K.; Schmitt, Russell J.; Holbrook, Sally J.
Abstract: The degree to which population fluctuations arise from variable adult survival relative to variable recruitment has been debated widely for marine organisms. Disentangling these effects remains challenging because data generally are not sufficient to evaluate if and how adult survival rates are regulated by stochasticity and/or population density. Using unique time series for a largely unexploited reef fish, we found both population density and stochastic food supply impacted adult survival. The estimated effect of variable survival on adult abundance (both mean and variability) rivalled that of variable recruitment. Moreover, we show density‐dependent adult survival can dampen impacts of stochastic recruitment. Thus, food variability may alter population fluctuations by simultaneously regulating recruitment and compensatory adult survival. These results provide an additional mechanism for why intensified density‐independent mortality (via harvest or other means) amplifies population fluctuations and emphasises need for research evaluating the causes and consequences of variability in adult survival.